PENGARUH REPUTASI PERUSAHAAN & SOSIAL MEDIA TERHADAP MINAT MELAMAR KERJA GENERASI Z: (STUDI KASUS MAHASISWA POLITEKNIK STIBISNIS TEGAL) - Nurlaeli, Fenti; Heriman Setio, Alfred; Caludya, Merisa (Perwira Journal of Economics & Business, 2025)
Companies find it difficult to maintain a quality workforce because generation Z likes to change workplaces in a short period of time. In fact, the company's success can be seen from the quality of its services, products, and ability to attract and retain a quality workforce. The purpose of this study is to find out the extent to which company reputation and social media affect the interest in applying for jobs in generation z, especially students of Stibisnis Tegal Polytechnic. This study uses a quantitative method with a population of 68 Stibisnis Polytechnic students in 2021 – 2023.The sampling technique used in this study is using nonprobability sampling with purposive sampling technique. The results of the study explain that company reputation and social media have a significant influence on the interest in applying for jobs of generation z in Stibisnis Tegal Polytechnic students both partially and simultaneously.Based on the results of the study, this indicates that the effective application of company reputation and social media can increase the interest in applying for jobs in Stibisnis Polytechnic students.